Landslide Susceptibility Mapping of the Kendeng Zone in Bojonegoro Regency using Geographic Information Systems - Arya Kusuma Hadi; Mrabawani Insan Rendra; Zainuddin Zainuddin; Mohammad Zainul Ikhwan; Herta Novianto (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
The Kendeng Zone in Bojonegoro Regency has a high potential for landslides due to its geological conditions and extreme tropical climate. This study aims to map landslide susceptibility levels using Geographic Information Systems (GIS). The research employs the Weighted Overlay method, which integrates multiple parameters. The study utilizes secondary data collected between 2021 and 2024, including rainfall records from BBWS, soil and rock maps from RTRW, and land cover data derived from RTRW. The analysis is conducted by assigning weights to each parameter to produce a landslide susceptibility zoning map. The results indicate that the Kendeng region is classified into four susceptibility levels: low, moderate, high, and very high. The area classified as having very high susceptibility covers 5,852.43 hectares, distributed across the Sekar, Gondang, and Temayang sub-districts. While this method provides a comprehensive spatial overview, the study is limited by the resolution of the available datasets and the expert-based subjectivity in weighting factors. The implications of this study highlight the need for increased attention in areas with high and very high susceptibility levels. The local government and communities should enhance preparedness, implement mitigation measures, and develop an early warning system to reduce landslide risks and impacts. Furthermore, the mapping results can serve as a basis for prioritizing areas requiring further intervention, such as reforestation, drainage improvements, and more sustainable land use.